2022
DOI: 10.3389/fmicb.2021.833054
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Convergent IGH Signatures and Severity of COVID-19 Patients by Next-Generation Sequencing of B-Cell Repertoire

Abstract: ObjectTo reveal convergent IGH signatures and the association with severity of coronavirus disease 2019 (COVID-19) patients.MethodA total of 25 COVID-19 inpatients were classified into three clinical conditions: mild, severe, and critical. We analyzed convergent IGH signatures by ImmuHub® B-cell receptor (BCR) profiling system.ResultsIGH singleton frequency in patients is significantly lower than that of healthy donors (HDs). The clonality index of IGH in patients is significantly higher than that in HDs. Neve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Ma et al 43 found that the clonal expansion of BCR‐CDR3 was more pronounced in 33 symptomatic COVID‐19 patients than in 5 asymptomatic and 11 healthy controls. Multiple other laboratories have reported the same association 44–47 …”
Section: Bcr‐cdr3 Features Changes and Significance In Sars‐cov‐2 Inf...mentioning
confidence: 69%
See 3 more Smart Citations
“…Ma et al 43 found that the clonal expansion of BCR‐CDR3 was more pronounced in 33 symptomatic COVID‐19 patients than in 5 asymptomatic and 11 healthy controls. Multiple other laboratories have reported the same association 44–47 …”
Section: Bcr‐cdr3 Features Changes and Significance In Sars‐cov‐2 Inf...mentioning
confidence: 69%
“…Multiple other laboratories have reported the same association. [44][45][46][47] The clonality changes of BCR-CDR3 in SARS-CoV-2 vaccine recipients are similar to those in infected individuals. BCR-CDR3 clonality significantly expanded at 14 days after the Ad5-nCoV vaccination 48 ; mRNA vaccine recipients had significantly clonal expanded memory B cells.…”
Section: Bcr-cdr3 Monitoring and Analysis Methods After Sars-cov-infe...mentioning
confidence: 80%
See 2 more Smart Citations